„Nie matura, lecz chęć szczera zrobi z ciebie oficera”, czyli rola przyzakładowego szkolnictwa w kształceniu kadr RBP/MBP/MSW (1944–1990) - Jusupović, Adrian (Dzieje Najnowsze, 2015)
Forget the Matura – Sincere Intentions Will Make You an Officer, or the Role of the Professional Training of the Cadres of the Ministry of Public Security/Ministry of Internal Affairs (1944–1990) Six fundamental periods may be distinguished while analysing the activity of the heads of the Ministry of Internal Affairs in 1944–1990, intent on improving the training of its functionaries: 1) 1944–1947, training cadres for the emergent Ministry of Public Security; 2) 1947– 1957, filling gaps in the comprehensive knowledge at the disposal of staff members by creating elementary and secondary schools for functionaries, opening libraries in Voivodeship and County Offices of Public Security, and guaranteeing an influx of trained cadres by setting up the institution of ministerial scholarships; 3) 1957–1962, formal completion of the comprehensive education of the functionaries; 4) 1963–1969, secondary school graduation certificates (evidence of passing the matura matriculation exam) became (at least in theory) a condition necessary for promotion to the rank of an officer; 5) 1969–1974, establishing higher education centres (the Part Time– Full Time Vocational Administration Course, the Officer Academy in Legionowo and the Officer Academy in Szczytno, the Academy of Internal Affairs); from 1972 it was recommended that young functionaries wishing to be promoted to the rank of officers should have higher education, and from 1974 secondary education was required of all Security Service and Citizens’ Militia functionaries; 6) 1975–1990 – a period of specialist training of officers in Ministry higher schools, and of ensigns – in Ensign Academies; only the Academy of Internal Affairs was entitled to award a master’s degree and was attended by functionaries intended for key functions.